(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article discusses the issues of increasing the efficiency of flat solar air heaters using heat exchange intensifiers. The author presents the main methods for increasing the heat transfer intensity from the absorber to the heated air in a flat solar collector, which are associated with flow separations from the absorber wall to the near-wall airflow, which practically has a low level of turbulence.